Correlation Of Age Factors With Incidence Rates Of Benign Enlarged Prostate Disease At Royal Prima Rsu In 2022 - Maysah Situmorang, Enjela; Ferdinand Ginting, Sahna; M. Chairul, M. Chairul (Riviera Publishing, 2023)
Benign prostatic hyperplasia is a condition where stromal and epithelial contributions are proliferative. The clinical features of benign prostatic hyperplasia are prostate enlargement, lower urinary tract complaints, and bladder obstruction. Several factors are thought to increase the risk of benign prostate hyperplasia, including age, family history, obesity, physical activity, diabetes, diet, smoking and alcohol consumption. This study aims to determine the relationship between age factors and the incidence of benign prostatic hyperplasia disease at RSU Royal Prima Medan. This study used quantitative research with a cross-sectional approach. The sampling technique in this study used a total sampling technique. This study analyzed a sample of 32 data using univariate and bivariate tests using Chi-Square. Based on the univariate test, it is known that the incidence of benign prostatic hyperplasia mostly occurs at the age of 61-70 years, as many as 15 people (46.9%). Based on the results of ultrasound, the size of the prostate volume is mostly 61 - 80 ml, as many as 15 people (46.9%). Based on the bivariate test using Chi-Square, the p-value is 0.023 (p<0.05), so it can be concluded that there is a significant relationship between age and benign prostatic hyperplasia.